PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 – 2017 - Murowadatul Azizah, 15.05.52.0360; Wahyu Widati, Lisyorini (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the influence of liquidity, leverage, profitability, sales growth on financial distress. The data used in this research are secondary data, in the form of company financial statements. And to find out the variables that most influence the broad disclosure of financial statements. The number of companies studied was 451 companies for 3 years, so the number of samples was 222 samples. The sampling method used in this study was purposive sampling using certain criteria. The data was then tested with descriptive statistics, feasibility of the model, overall test model, chi square test, cox test and snell's R square and nagelkerke’s R square. 2x2 classification table, logistic regression analysis, using SPSS 19 for windows. The results of the analysis can be concluded that liquidity and a significant negative effect on financial distress, leverage has a significant positive effect on financial distress, profitability and sales growth do not affect financial distress.